Sources and inheritance of earliness in tropically adapted indeterminate common beans - White, Jeffrey W.; Singh, Shree P. (Springer, 1991)
Nineteen early maturing, indeterminate common bean parents were crossed with a tester line of normal maturity. All parents, F1 hybrids, F2's, and backcross generations were evaluated at CIAT-Palmira, Colombia. All 19F1 populations flowered and matured almost as early as the respective early parent (mean of 61 vs 59 days). The F2 populations were slightly less early (63 days), but were still earlier than the mean of the two parents (65 days). Additive effects for days to maturity were usually larger than dominance or interaction effects. Narrow sense heritability for days to flower and maturity were high (greater than 0.67), while heritabilities of absolute and relative duration of pod filling were low (0.17 to 0.50). Also, our data indicated that for each day of increase in earliness, yield potential will decrease 74 kg/ha.